The Role of Ulama in the Development Communication of the Family Planning Program - Latif Ahmad Fauzan; Windri Saifudin; Augustin Mustika Chairil (Jurnal Spektrum Komunikasi, 2023)
One of the problems causing society's prosperity low level is the imbalance of population growth, economic growth, and health. BKKBN (National Family Planning Coordinating Board) has a role to measure and control the growth of Indonesia's population through the KB (The Family Planning Program). In Yogyakarta, especially in Wonokromo Village, Pleret, Bantul Regency, the implementation and socialization of KB program had some obstacles because most people thought that the program seemed to be contrary to the way of the Islamic rules. Therefore, the ulama have a crucial role in changing of community’s perspective on KB in the context of Islam. Based on the background of those problems, the researcher was interested in this topic of research to understand Ulama’s role for BKKBN and the community from communication science perspective, especially Development Communication. The qualitative descriptive method is the basic method in this research. The result of the research is that Ulama play an important role in the Interpersonal Communication process with the BKKBN, and play a major role in disseminating the family planning program to the Wonokromo Community. Ulama played a role in interpreting and communicating the Family Planning Program in accordance with the Islamic perspective, so that people can accept and implement the program.